Beyond surveys: How alternative data can measure the health of the labor market - Loujaina Abdelwahed; Ritesh Baldva; Lisa Simon (EconPol Forum, 2026)
The private sector offers reliable labor market data that policymakers, investors, and the public can use to guide their decisions. Revelio Labs provides monthly labor stats from billions of work records, tracking employment, openings, turnover, and pay. Alternative data is created beyond the goal of measurement, thereby avoiding survey bias and offering timely, cost-effective insights. Job estimates from profiles need cleaning, title mapping, and models that adjust for sampling bias and reporting lag. Job openings deduplicated across various sources provide a forward-looking view of demand and make it possible to estimate pay trends.
Keywords: 330